1995
DOI: 10.1002/pros.2990270108
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical characterization of explant cultures of human prostatic stromal cells

Abstract: The study of stromal-epithelial interactions greatly depends on the ability to culture both cell types separately, in order to permit analysis of their interactions under defined conditions in reconstitution experiments. Here we report the establishment of explant cultures of human prostatic stromal cells and their immunocytochemical characterization. As determined by antibodies to keratin and prostate specific acid phosphatase, only small numbers (< 5%) of epithelial cells were present in primary cultures; su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Earlier work has indicated that the proportion of smooth muscle decreases in the stroma of tumour samples (Hayward et al, 1997) but we did not find significant differences in the cell composition of primary stromal cultures, even of stromal cultures from poorly differentiated tissue. Stromal cultures were used which were unpassaged, therefore giving rise to a mixed population of cells, and while this may be considered ill-defined, we wished to use this as a model to mimic the cell populations present in the patient and also to avoid using later passaged cultures whose characteristics and growth stimulating effects become altered (Kooistra et al, 1995a(Kooistra et al, , 1995bPasternack et al, 1997). Further investigation is required to isolate primary cultures of smooth muscle cells or fibroblasts alone and analyse their effects on epithelial cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work has indicated that the proportion of smooth muscle decreases in the stroma of tumour samples (Hayward et al, 1997) but we did not find significant differences in the cell composition of primary stromal cultures, even of stromal cultures from poorly differentiated tissue. Stromal cultures were used which were unpassaged, therefore giving rise to a mixed population of cells, and while this may be considered ill-defined, we wished to use this as a model to mimic the cell populations present in the patient and also to avoid using later passaged cultures whose characteristics and growth stimulating effects become altered (Kooistra et al, 1995a(Kooistra et al, , 1995bPasternack et al, 1997). Further investigation is required to isolate primary cultures of smooth muscle cells or fibroblasts alone and analyse their effects on epithelial cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Cussenot et al (1994) reported that cultures of normal prostatic epithelial cells did not make the basement membrane protein, type IV collagen. Cultured prostatic epithelial cells aberrantly make the mesenchymal-associated extracellular matrix protein, vimentin, but this is true of most cultured epithelial cells and is apparently a common artifact of in vitro propagation (Sherwood et al 1989, Kooistra et al 1995, Goossens et al 2002.…”
Section: Basal Epithelial Cellsmentioning
confidence: 99%
“…Although these malignant or transformed cell lines represent more or less appropriate model systems of prostatic epithelium, adequate nonmalignant and highly differentiated epithelial cell lines have only rarely been obtained [13][14][15][16][17]. The same applies to stromal cells, which are most often classified as either SMC or fibroblasts, but only a limited number of investigators have tried to characterize more precisely the stromal cells grown in vitro [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Prostatic stroma is mainly composed of smooth muscle cells (SMC) [4] and fibroblasts [5], but relatively little is known about the functional activity of these cells in vitro. Recently, some reports were published [6][7][8][9] showing that prostatic stromal cells, characterized as either fibroblasts or smooth muscle cells, can be obtained from surgical prostate specimens by combined mechanical and enzymatic dissociation and propagated in their differentiated state at least for a limited number of passages.…”
Section: Introductionmentioning
confidence: 99%